To the Castle and back - Havel, Václav 1936-2011 (Knopf, 2007)
As writer, dissident, and statesman, Havel played an essential part in the changes that occurred in Central Europe during the last decades of the twentieth century, and became a powerful intellectual and political force for the reestablishment of democratic principles and institutions. Now, in this memoir, he recollects the pivotal experiences and ideas of his remarkable life. Known in his native Prague for his theatrical productions, and imprisoned for his anticommunist views, Havel emerged on the international stage in 1989 as the elected president of Czechoslovakia. He writes with eloquence and candor about his transition from playwright to politician, and the surreal challenges of governing a young democracy. But the scope of his writing extends far beyond the circumstances he faced in his own country. He shares his thoughts on the future of the EU, the reach of the American superpower, and the role of national identity in today's world.--From publisher description.
Includes interview with Karel Hvížd̒ala.
Keywords: Havel, Václav; Havel, Václav -- 1936-2011; Dissidents - Tchécoslovaquie - Biographies; Dramaturges tchèques - 20e siècle - Biographies; Présidents - République tchèque - Biographies; Présidents - Tchécoslovaquie - Biographies; Politik; République tchèque - Politique et gouvernement - 1993-; Tchécoslovaquie - Politique et gouvernement - 1968-1989; Tchécoslovaquie - Politique et gouvernement - 1989-1992; Tsjechië; Tschechische Republik; Tschechoslowakei; Czechoslovakia -- Politics and government -- 1989-1992; Czech Republic -- Politics and government -- 1993-; Autobiografie -- 1993-2005; Fiktionale Darstellung